Enoxaparin-induced cutaneous panniculitis in a pregnant female - Narula, Shubhank (Indian Journal of Case Reports, 2024)
Low-molecular-weight heparins (LMWHs) are currently used as an antithrombotic prophylactic therapy during pregnancy and in post-surgery patients. The safety of various drugs in pregnancy has always been a matter of concern. Enoxaparin, being associated with low fetal and neonatal complications, is used extensively to improve the outcomes in high-risk pregnancies. The duration of treatment with LMWH in pregnancy is generally long; hence, strict monitoring of side effects should be done. We report a case of a 25-year-old pregnant female who experienced painful, erythematous skin necrosis and panniculitis after prophylactic administration of enoxaparin at multiple sites subcutaneously.